The Location of LPG Filling Stations and Potential Risks of Incidents - Varta, Ondrej; Krocova, Sarka (Communications - Scientific Letters of the University of Zilina, 2016)
The risk of unsuitable placement of LPG (i.e. Liquid Petroleum Gas) propane-butane filling stations in densely populated areas or in the immediate vicinity of busy roads may have, in the event of fire or explosion, incalculable consequences in terms of fatal or serious accidents and cause considerable economic damage to property. As a consequence, the positioning of any such LPG filling station should always be of crucial importance already in the filling station planning stage and its placement should be carefully assessed. The present paper aims at outlining a particular method of evaluating risks resulting from incorrect placement of an LPG filling station, including potential consequences. One such approach to assessment of installation safety of LPG filling stations is to implement the so called ALOHA screening method. This paper shall demonstrate practical implementation of the ALOHA screening, and that with regard to infrastructure, it is not always possible to find a suitable and safe location for LPG filling stations.
Keywords: ALOHA; safe LPG filling station location; emergencies; safe distance